Comparison of the Newborn Infant Parasympathetic Evaluation (NIPE™) index to changes in heart rate to detect intraoperative nociceptive stimuli in healthy and critically ill children below 2 years: An observational study. Issue 7 (5th April 2022) - Neumann, Claudia; Babasiz, Tamara; Straßberger‐Nerschbach, Nadine; Schindler, Ehrenfried; Reuter, Christian; Weinhold, Leonie; Wittmann, Maria; Hilbert, Tobias; Klaschik, Sven
Abstract: Background: The validity of current tools for intraoperative objective assessment of nociception/antinociception balance during anesthesia in young and very young surgery children is unknown. Aim: Primary aim of the study was to test the hypothesis that the Newborn Infant Parasympathetic Evaluation (NIPE) index performs better in indicating nociception in anesthetized children below 2 years than changes in heart rate. Secondary aims were to evaluate associations between intraoperative changes in NIPE index values and postoperative pain and emergence delirium. Methods: Fifty‐one children aged <2 years who underwent surgery were included in this prospective observational study. Patients were assigned to either group 1 (healthy children, n  = 31) or group 2 (critically ill, ventilated premature infants and neonates, n  = 20). The NIPE index and heart rate in response to three defined nociceptive stimuli were continuously recorded. Two different scales, Kindliche Unbehagens‐ und Schmerzskala (KUS) and Pediatric Anesthesia Emergence Delirium (PAED) as well as a Pain Questionnaire were used to assess postoperative pain levels and emergence delirium. Results: In total, 110 nociceptive events were evaluated. The analysis revealed a statistically significant association between a decrease in the NIPE index and all nociceptive stimuli, with a sensitivity of 92% and a specificity of 96%. The mean percentage decrease ranged from approx. 15%–30% and was highly statistically significant in both groups and for each of the nociceptive events except for venous puncture ( p  = .004). In contrast, no consistent change in heart rate was demonstrated. The KUS and PAED scale scores were significantly associated with the duration of anesthesia ( p  = .04), but not with intraoperative NIPE depression. Conclusion: The NIPE index was reliable for assessing intraoperative nociception in children aged <2 years and was more reproducible for detecting specific nociceptive stimuli during general anesthesia than heart rate. An effect on postoperative outcome is still elusive.